2018
DOI: 10.1038/s41598-018-25929-0
|View full text |Cite
|
Sign up to set email alerts
|

Xiaoshuan enteric-coated capsule alleviates cognitive impairment by enhancing hippocampal glucose metabolism, hemodynamics and neuroplasticity of rat with chronic cerebral hypoperfusion

Abstract: Chronic cerebral hypoperfusion (CCH) is identified as a critical risk factor of dementia in patients with cerebrovascular disease. Xiaoshuan enteric-coated capsule (XSECC) is a compound Chinese medicine approved by Chinese State Food and Drug Administration for promoting brain remodeling and plasticity after stroke. The present study aimed to explore the potential of XSECC to improve cognitive function after CCH and further investigate the underlying mechanisms. CCH was induced by bilateral common carotid arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
(50 reference statements)
1
4
0
Order By: Relevance
“…In light of this, we investigated whether the enhancement in axonal remodeling by XSEC + EE combination might contribute to the improvement in learning and memory performance in the MWM task. Our results were consistent with previous reports and indicated that XSEC and EE monotherapies improved spatial reference learning and memory performance, as evaluated by the MWM test (Dahlqvist et al, 2004;Li et al, 2018b). Interestingly, the combined action of both permitted faster adaptation to a changed testing environment, as revealed in the platform-switched learning trial.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In light of this, we investigated whether the enhancement in axonal remodeling by XSEC + EE combination might contribute to the improvement in learning and memory performance in the MWM task. Our results were consistent with previous reports and indicated that XSEC and EE monotherapies improved spatial reference learning and memory performance, as evaluated by the MWM test (Dahlqvist et al, 2004;Li et al, 2018b). Interestingly, the combined action of both permitted faster adaptation to a changed testing environment, as revealed in the platform-switched learning trial.…”
Section: Discussionsupporting
confidence: 93%
“…XSEC was dissolved in physiological saline to a concentration of 28 mg/mL before use. The dose of XSEC (140 mg/kg) used in this study was determined based on our previous study (Li et al, 2018b).…”
Section: Preparation Of Xsecmentioning
confidence: 99%
“…Low cerebral blood flow (CBF) in CCH changes the homeostasis of hemodynamics and reduces the availability of oxygen, glucose, and other nutrients in the brain. This leads to disturbances in the homeostasis of energy metabolism [2, 3], which in turn leads to cerebrovascular remodeling, degeneration of the neurovascular unit and trophic coupling [4], energy loss in neurons, and vulnerability to the internal and external environment.…”
Section: Introductionmentioning
confidence: 99%
“…The animals in vehicle, EE and control group were given saline at 5 ml/kg in the same manner. Determination of the doses of XSEC used in the present study was based on our previous study which indicated that the administration of XSEC at 140 mg/kg of body weight improves cognitive function and cerebral hemodynamics in a chronic cerebral hypoperfusion rat model (Li M.Z. et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…XSEC is authenticated and standardized based on marker compounds in the Chinese Pharmacopeia (Chinese Pharmacopoeia Commission, 2015), and is approved for treating ischemic stroke by the China Food and Drug Administration. XSEC has multi-target neurovascular protective effects on ischemic stroke, including restoring cerebral blood flow (CBF), preserving the neurovascular unit, and improving neuronal/glial metabolism (Zhang et al, 2016; Li M.Z. et al, 2018).…”
Section: Introductionmentioning
confidence: 99%